Descriptive Study of The Nature of Educational Science - Arditya Prayogi; Riki Nasrullah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
A review of the nature of education is a review that must be holistic. A holistic review regarding the nature of education is needed considering that education is a universal thing that cannot be separated from human life. This article was written using a qualitative approach supported by using a literature study method by reviewing literature related to the theme of the article. From the results of the study, it is clear that the field of study of educational science is the educational situation. The method used is an empirical method, equipped with rational and transcendental analysis, to open the horizon of meaning of educational phenomena. The recognition that education is a science has implications for educational practice for both educational scientists and anyone working in the field of education. In the end, educational science is useful for human welfare because educational science cannot be separated from studying and researching the role of values and norms in human life, especially educational activities themselves.